Edible medicinal and non-medicinal plants : Volume 6,Fruits - Lim, Tong Kwee (Springer, 2013)
"This book... covers edible fruits/seeds used fresh, cooked or processed into other by-products, or as vegetables, cereals, spices, stimulant, edible oils and beverages. It covers selected species from the following families: Sapindaceae, Sapotaceae, Schisandraceae, Solanaceae, Thymelaeaceae, Urticaceae, Vitaceae and Winteraceae." Back cover.